PENINGKATAN KAPABILITAS EKS TENAGA KERJA INDONESIA (TKI) DESA PANDES DAN GONDANG KECAMATAN CEPIRING KABUPATEN KENDAL MELALUI SEKTOR INDUSTRI KECIL EKONOMI KREATIF TERBARUKAN (GREEN ECONOMIC SMEs) - Asep Rokhyadi; Subarjo .; Almunfarijah . (Universitas Muhammadiyah Ponorogo, 2017)
The second year (2017) Science Program for the Region (IbW) is a priority in the program in the previous year that is in 2016. The program in the first year has been fruitful and by the team will be developed further. The application of science and technology in this program in the past year has resulted in both services and products in the form of, the formation of the group, the formation of the bamboo creative industrial sub-group, the creative economy of beverages and chips, small wood industry, and printing business. The entire sector is based on renewable raw materials (green raw material). These results have had a significant impact on increasing incomes, updating science and technology in the community, regional economic growth, togetherness in managing creative productive economy in the group region.To develop the Science and Technology program for the Region (IbW) hereinafter, this program aims to create more independence and welfare of the community in Pandes and Gondang villages, especially the ex-Indonesian Migrant Workers (TKI) through empowerment programs that have been established by synergizing the college and Government counseling Kendal district as set forth in the RPJMD, and secondly, providing coverage in overcoming unemployment over solutions to problems faced by district and community Governments that directly potentially affect income and welfare improvements. In order to achieve these objectives, through the IbW program in 2017 the method used is to recruit new members (now 18 SMEs) to the established groups in order to have broader effects, extension and empowerment for industrialization of bamboo products innovation, creative drinking industry innovation and chips, wood industry groups, and printing business groups. Achievement and Motivation Training (AMT) method was also conducted to increase entrepreneurial motivation. The activity is carried out continuously with a plan of three consecutive years, this is the second year.